Polygenis (Polygenis) platensis (Jordan & Rothschild) (Siphonaptera: Rhopalopsyllidae, Rhopalopsyllinae), a New Record in Brazil - Linardi, Pedro M. (2005)
Polygenis (Polygenis) platensis s. l. (Jordan & Rothschild) is recorded for the first time from Brazil in the municipalities of Capão da Canoa, Tramandaí and Osório, RS. New host records for this flea include Ctenomys flamarioni (Travi) and Ctenomys minutus (De Blainville). Morphological variations were also observed among the flea specimens collected on the same species of host at the same municipality, evidencing some hybridization between the two subspecies and disabling the determination of the subspecific status. The number of known species of Brazilian Siphonaptera is now 60.